Risk factors for resignation from work after starting infertility treatment among Japanese women: Japan-Female Employment and Mental health in Assisted reproductive technology (J-FEMA) study. (3rd December 2020) - Imai, Yuya; Endo, Motoki; Kuroda, Keiji; Tomooka, Kiyohide; Ikemoto, Yuko; Sato, Setsuko; Mitsui, Kiyomi; Ueda, Yuito; Deshpande, Gautam A; Tanaka, Atsushi; Sugiyama, Rikikazu; Nakagawa, Koji; et al.
Abstract : Objective: To elucidate the risk factors associated with resignation from work of Japanese women undergoing infertility treatment. Methods: A total of 1727 female patients who attended a private fertility clinic in Japan participated in the Japan-Female Employment and Mental health in Assisted reproductive technology study. Questions related to demographic, clinical and socioeconomic characteristics were employed in the questionnaire. Out of the 1727 patients, 1075 patients who were working at the time of initiating infertility treatment and felt infertility treatment incompatible with work were included in the analysis. Risk factors for resignation were assessed by using multivariable logistic regression models. Results: Among 1075 working women who started infertility treatment, 179 (16.7%) subsequently resigned. Multivariable-adjusted ORs for resignation in those with lower educational background and infertility for ≥2 years were 1.58 (95% CI: 1.07 to 2.34) and 1.82 (95% CI: 1.15 to 2.89), respectively. The OR for resignation in non-permanent workers undergoing infertility treatment was 2.65 (95% CI: 1.61 to 4.37). While experiencing harassment in the workplace approached significance, lack of support from the company was significantly associated with resignation after starting infertility treatment, with ORs of 1.71 (95% CI: 0.98 to 2.99) and 1.91 (95% CI: 1.28 to 2.86), respectively. Conclusion: One-sixth of women resigned after starting infertility treatments. It was found that factors related to education, infertility duration and work environment were significantly associated with resignation. Reducing the physical and psychological burden endured by women, for example, by increasing employer-provided support, is vitally important in balancing infertility treatment with maintenance of work life.